2011
DOI: 10.1097/gme.0b013e318208fb0d
|View full text |Cite
|
Sign up to set email alerts
|

S-equol and the fermented soy product SE5-OH containing S-equol similarly decrease ovariectomy-induced increase in rat tail skin temperature in an animal model of hot flushes

Abstract: The results of this animal model of hot flushes suggest that S-equol is one of the primary components of SE5-OH and that both SE5-OH and S-equol represent promising alternatives for the treatment of menopausal symptoms. Clinical research is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…(13) Kimira et al (26) indicated that the preventive effect of S -equol on bone loss caused by OVX was greater than that of racemic equol. In addition, Yoneda et al (27) reported that S -equol improved the increased tail-skin temperature in a rat model of hot flushes. S -equol has been shown to be rapidly absorbed and excreted from the body in humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…(13) Kimira et al (26) indicated that the preventive effect of S -equol on bone loss caused by OVX was greater than that of racemic equol. In addition, Yoneda et al (27) reported that S -equol improved the increased tail-skin temperature in a rat model of hot flushes. S -equol has been shown to be rapidly absorbed and excreted from the body in humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…Since the fermented supplement contained other components of soy, including soy protein, genistein, and unmetabolized daidzein, the decrease in VMS may have been due to these components of the fermented soy. However, a recent report using the ovariectomized rat suggests that it is S-equol in SE5-OH that accounts for its therapeutic effect [ 31 ] . In this study, ovariectomy was associated with approximately a 0.8 °C increase in tail temperature.…”
Section: A Dietary Supplement Containing S-equol (Se5-oh) and Menopaumentioning
confidence: 98%
“…No significant changes compared with control were instead observed in a 35-day study in which animals were treated with either S-equol or a soy germ extract, both providing a dose of 11.5 mg/kg bw/day of S-equol (Yoneda et al, 2011 The authors reported that animals in the SPI groups were administered soy protein isolate (SPI) at 100 and at 200 g/kg diet (low SPI and high SPI, respectively). The SPI used contained 2.14 mg/g aglycone from isoflavones (genistein, 1.10 mg/g; daidzein, 0.84 mg/g and glycitein, 0.20 mg/g).…”
Section: Endpoint: Histo(patho)logymentioning
confidence: 99%
“…The isomer S-equol and a fermented soy germ product containing S-equol were tested in one study in rats at a single dose of 11.7 mg/kg bw/day (Yoneda et al, 2011).…”
Section: Range Of Doses Used In the Animal Studies Included In The Symentioning
confidence: 99%